2012
DOI: 10.2139/ssrn.2165146
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Monetary Union in the Gulf Cooperation Council: What Lessons for Regional Cooperation?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…The population in Oman increased from 3.04 million in 2010 to 4.63 million in 2017 with a Compounded Annual Growth Rate (CAGR) of 6.20%. Due to the increasing population of Oman, the forecast of United Nation's Food and Agriculture Organization (FAO), indicated that the food imports of Oman are expected to touch $4.8 billion by 2020, when compared to $2.1 billion in 2010, given, that 60% of its food needs are met by international markets (Takagi, 2012). In the current situation, Oman is capable of financing the imports to meet the food security of its population.…”
Section: Population Growthmentioning
confidence: 99%
“…The population in Oman increased from 3.04 million in 2010 to 4.63 million in 2017 with a Compounded Annual Growth Rate (CAGR) of 6.20%. Due to the increasing population of Oman, the forecast of United Nation's Food and Agriculture Organization (FAO), indicated that the food imports of Oman are expected to touch $4.8 billion by 2020, when compared to $2.1 billion in 2010, given, that 60% of its food needs are met by international markets (Takagi, 2012). In the current situation, Oman is capable of financing the imports to meet the food security of its population.…”
Section: Population Growthmentioning
confidence: 99%